Graduate Curriculum for Biological Information Specialists: A Key to Integration of Scale in Biology - Carole L. Palmer; Bryan P. Heidorn; Dan Wright; Melissa H. Cragin (International Journal of Digital Curation, 2008)
Scientific data problems do not stand in isolation. They are part of a larger set of challenges associated with the escalation of scientific information and changes in scholarly communication in the digital environment. Biologists in particular are generating enormous sets of data at a high rate, and new discoveries in the biological sciences will increasingly depend on the integration of data across multiple scales. This work will require new kinds of information expertise in key areas. To build this professional capacity we have developed two complementary educational programs: a Biological Information Specialist (BIS) masters degree and a concentration in Data Curation (DC). We believe that BISs will be central in the development of cyberinfrastructure and information services needed to facilitate interdisciplinary and multi-scale science. Here we present three sample cases from our current research projects to illustrate areas in which we expect information specialists to make important contributions to biological research practice.